Training Effect Of Self Efficacy Of Career Decision Making Self Efficacy (CDMSE) And N-Ach On Student SMAN 01 Pasuruan East Java - Febriantomo, Eko Hari; Suharnan, - (Persona:Jurnal Psikologi Indonesia, 2015)
This study aims to test the effectiveness of self-efficacy training to improve confidence in making career decisions (CDMSE) and achievement motivation (N-Ach) in 60 high school students. Through experimental approaches, obtained by 30 students as the experimental group and 30 students as a control group. Data were collected through questionnaires tests before and after the test, which is then analyzed by t-test. As the results of pre-test and post-test on a scale CDMSE test for the experimental group obtained probability value of 0.000 (p <0.05), which means that the hypothesis of no effect of self-efficacy training to CDMSE acceptable. so that self-efficacy training gives pangaruh to decision making career in high school students to determine the level of studies. And the results of the analysis of pre test and post test N-Ach-scale test in the experimental group obtained probability value of 0.000 (p <0.05), which means that in the experimental group there are differences in the results of pre-test to post-test. So the hypothesis that there is the influence of self-efficacy training to N-ach proven.